2021
DOI: 10.1017/ehs.2021.12
|View full text |Cite
|
Sign up to set email alerts
|

When do people prefer dominant over prestigious political leaders?

Abstract: Previous research has sought to explain the rise of right-wing populist leaders in terms of the evolutionary framework of dominance and prestige. In this framework, dominance is defined as high social rank acquired via coercion and fear, and prestige is defined as high social rank acquired via competence and admiration. Previous studies have shown that right-wing populist leaders are rated as more dominant than nonpopulist leaders, and right-wing populist / dominant leaders are favoured in times of economic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Across this body of research, we observed a consistent pattern: People supported leaders who adopt a prestige-based leadership strategy over those who use dominance to lead. Based on the existing evolutionary literature on leadership selection, one might be tempted to draw the conclusion that certain contexts cause people to prefer dominant leaders over other types of leaders (Jiménez et al, 2021; Kakkar & Sivanathan, 2017; c.f., Laustsen & Petersen, 2017) . However, in the current work, prestigious leaders were preferred even during times of intergroup conflict and competition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across this body of research, we observed a consistent pattern: People supported leaders who adopt a prestige-based leadership strategy over those who use dominance to lead. Based on the existing evolutionary literature on leadership selection, one might be tempted to draw the conclusion that certain contexts cause people to prefer dominant leaders over other types of leaders (Jiménez et al, 2021; Kakkar & Sivanathan, 2017; c.f., Laustsen & Petersen, 2017) . However, in the current work, prestigious leaders were preferred even during times of intergroup conflict and competition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current findings highlight the role of intergroup conflict, it is worth noting that leadership preferences may shift in response to contexts other than intergroup conflict that were not manipulated in the current work. For example, economic uncertainty may cause people to feel that they lack personal control, which may underlie support for dominance (Kakkar & Sivanathan, 2017; c.f., Jiménez et al, 2021). Another important caveat is that the manipulations of social context used in the current work may have differed across studies in the degree of existential threat they implied to participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because of its sensitivity to experimental manipulation, we used a well-validated task based on first impressions of faces to study the effect of apolitical anger on leaders' preferences. However, while this experimental protocol provides insight into the type of traits that may be valued in leaders in different contexts, other factors such as political affiliation play a more central role in real elections, sometimes interacting with the perception of candidates' personality traits 21 , 50 . Nevertheless, our results suggest that emotional factors, in addition to well-identified contextual factors such as war and social threats, can influence our preferences for particular leaders.…”
Section: Discussionmentioning
confidence: 99%
“…While prestigious leaders are preferred when there are intragroup conflicts, dominant leaders are preferred when there are intergroup conflicts in which in-group members could benefit from antagonizing out-group members (Halevy et al, 2012;Maner, 2017). That is, during intergroup conflicts, displaying dominant actions and traits can foster increased admiration and respect (e.g., Jiménez et al, 2021). Indeed, dominance and morality seem to converge when it comes to combative heroism or warriorship in certain instances (Bai, 2017).…”
Section: Studymentioning
confidence: 99%